A Moss 2-Oxoglutarate/Fe(II)-Dependent Dioxygenases (2-ODD) Gene of Flavonoids Biosynthesis Positively Regulates Plants Abiotic Stress Tolerance - Wang, Huijuan; Liu, Shenghao; Fan, Fenghua; Yu, Qian; Zhang, Pengying (Frontiers in Plant Science, 2022)
Flavonoids, the largest group of polyphenolic secondary metabolites present in all land plants, play essential roles in many biological processes and defense against abiotic stresses. In flavonoid biosynthesis pathway, flavones synthase I (FNSI), flavanone 3-hydroxylase (F3H), flavonol synthase (FLS), and anthocyanidin synthase (ANS) all belong to 2-oxoglutarate/Fe(II)-dependent dioxygenases (2-ODDs) family, which catalyzes the critical oxidative reactions to form different flavonoid subgroups. Here, a novel 2-ODD gene was cloned from Antarctic moss Pohlia nutans (Pn2-ODD1) and its functions were investigated both in two model plants, Physcomitrella patens and Arabidopsis thaliana. Heterologous expression of Pn2-ODD1 increased the accumulation of anthocyanins and flavonol in Arabidopsis. Meanwhile, transgenic Pn2-ODD1 P. patens and Arabidopsis exhibited enhanced tolerance to salinity and drought stresses, with larger gametophyte sizes, better seed germination and root growth, respectively. Heterologous expression of Pn2-ODD1 in Arabidopsis also conferred the tolerance to UV-B and oxidative stress by increasing antioxidant capacity. Therefore, we showed that Pn2-ODD1 participated in the accumulation of anthocyanins and flavonol, and regulating the tolerance to abiotic stresses in plants, contributing to the adaptation of P. nutans to polar environment.